Effectiveness of an online SUpport PRogramme (SUPR) for older hearing aid users: study protocol for a cluster randomised controlled trial. Issue 5 (20th June 2017) - Meijerink, Janine FJ; Pronk, Marieke; Paulissen, Bernadette; Witte, Birgit I; Wouden, Bregje van der; Jansen, Vera; Kramer, Sophia E
Abstract : Background: An educational SUpport PRogramme called SUPR has been developed for hearing aid users (HAUs) and their communication partners (CPs) offering care beyond hearing aid fitting. SUPR teaches its users communication strategies, hearing aid handling skills and personal adjustment to hearing impairment. Methods/design: Using a cluster randomised controlled trial design, 70 Dutch hearing aid dispenser practices were randomised into hearing aid fitting (care as usual, 34 practices) and hearing aid fitting including SUPR (36 practices). The aim was to recruit a total of 569 older (aged 50+ years) first-time (n=258) and experienced (n=311) HAUs and their CPs. SUPR consists of a Practical Support Booklet and online material offered via email over a period of 6–7 months. The booklet provides practical information on hearing aids, advice on communication strategies and home exercises. The online material consists of educational videos on hearing aid functionality and usage, communication strategies and peer testimonials. Finally, noncommittal email contact with the dispenser is offered. Every HAU is asked to assign a CP who is advised to be involved intensively. Effect measurements for HAUs and their CPs will occur at baseline and at 6, 12 and 18 months follow-up via online questionnaires. The primary outcomes for HAUs will be the use of communication strategies as measured by the subscales of the Communication Profile for the Hearing Impaired. A process evaluation will be performed. Ethics and dissemination: The study was approved by the Dutch Institutional Review Board of the VU Medical University Center Amsterdam. This intervention could contribute to lowering the hearing impairment burden in our ageing society. The results will be disseminated through peer-reviewed publications and scientific conferences. Trial registration number: ISRCTN77340339; Pre-results.